EFFECT OF PН AND MINERALIZING PROPERTIES OF THE ORAL FLUID ON ENAMEL ACID RESISTANCE IN CHILDREN - Kaskova, L.F.; Mandziuk Т.B.; Godovanets, O.I.; Ulasevych, L.P.; Kuznіak L.V. (World of Medicine and Biology, 2019)
The present study was aimed to investigate the indices of рН, microcrystallization of the oral fluid in 7-9-year-old children with caries and without it, and possibility of occurrence of carious lesions with further use of the obtained results concerning the necessity to initiate preventive measures. The course of caries in 7-9-year-old children occurs against the ground of decrease of pH and saliva microcrystallization indices, and it is caused by reduced dental resistance to caries which is evidenced by the results of examination of the enamel acid resistance according to the enamel resistance test. The analysis of the obtained results demonstrated existence of a reverse correlation in 7-9-year-old children with caries between the index of enamel acid resistance and mineralizing potential (r= 0.73 – strong index) and рН (r= 0.66 – reverse considerable) of the oral fluid. These children presented direct strong connection between pH index and saliva mineralizing potential (r= 0.79). The results obtained promote the necessity to perform primary and secondary prevention directed to the improvement of homeostasis indices in the oral cavity which will enable to decrease prevalence and intensity of caries in children.